Gender-responsive design of bacteriophage products to enhance adoption by chicken keepers in Kenya - Campbell, Zoë A.; Njiru, Nelly; Mhone, Amos L.; Makumi, Angela; Moineau, S.; Svitek, Nicholas (MDPI, 2023)
Women and men keeping chickens in Kenya aspire to have a source of income, feed their families healthy food, and grow their businesses. Managing animal diseases and minimizing input costs enable their success. This study uses qualitative methods to recommend design opportunities for a veterinary product under development in Kenya that contains bacteriophages (phages) that target pathogenic Salmonella strains responsible for fowl typhoid, salmonellosis, and pullorum in chickens and foodborne illness in people. Our findings revealed the interplay between gender and two production systems: free-range and semi-intensive. Chicken keepers in both systems could benefit from phages combined with the orally administered Newcastle disease vaccine, one of the most commonly used preventive veterinary interventions, or phages as a treatment for fowl typhoid. Oral administration is less labor intensive, with greater benefits for women who have less control over family labor and reported doing more care tasks themselves. Men in free-range systems usually pay for veterinary inputs. In semi-intensive production systems, a phage-based product used prophylactically could be an alternative to expensive, intramuscular fowl typhoid vaccines. Keeping layers was common for women in semi-intensive systems, as they are more economically impacted by reduced laying caused by bacterial diseases. Awareness of zoonoses was low, but men and women were concerned about the negative health effects of drug residues in meat and eggs. Therefore, highlighting the lack of a withdrawal period for a phage product may appeal to customers. Antibiotics are used to both treat and prevent diseases, and phage products will need to do both to compete in the Kenyan market. These findings guide the ongoing design of a phage-based product with the goal of introducing a new veterinary product that meets the diverse needs of chicken keepers in Africa and serves as an alternative or complement to antibiotics.